Coisotropic hypersurfaces in Grassmannians. (March 2021) - Kohn, Kathlén
Abstract: To every projective variety X, we associate a list of hypersurfaces in different Grassmannians, called the coisotropic hypersurfaces of X . These include the Chow form and the Hurwitz form of X . Gel'fand, Kapranov and Zelevinsky characterized coisotropic hypersurfaces by a rank one condition on tangent spaces. We present a new and simplified proof of that result. We show that the coisotropic hypersurfaces of X equal those of its projectively dual variety, and that their degrees are the polar degrees of X . Coisotropic hypersurfaces of Segre varieties are defined by hyperdeterminants, and all hyperdeterminants arise in that manner. We generalize Cayley's differential characterization of coisotropy and derive new equations for the Cayley variety which parametrizes all coisotropic hypersurfaces of given degree in a fixed Grassmannian. We provide a Macaulay2 package for transitioning between X and its coisotropic hypersurfaces.